Four Moments of International Communication Research in the Cold War and Beyond - Ampuja, Marko (Javnost-The Public, 2019)
This article discusses the impact of the Cold War and its legacy on international communication research. Critically reconstructing the history of the Cold War in political-ideological terms, it demonstrates that this research area has been characterised by a battle between liberal internationalist theories and theories of imperialism, which has occurred in two stages. During the Cold War, Western liberal notions of modernisation were challenged by theories of media-cultural imperialism. The end of the Cold War led to a return of liberal notions in international communication research—though they appeared in a less Western-centric form—in association with globalisation theory. The article argues that with the demise of the post-Cold War globalisation zeitgeist and the return of major geopolitical conflicts, theories of “new imperialism”, which focus on the interplay between “capitalist” and “territorial” imperialism, offer a fruitful foundation for understanding the early twenty-first century international media and communication order.